2017
DOI: 10.1158/1078-0432.ccr-17-1185
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo PD-L1/PD-1 Pathway Blockade Reverses Dysfunction of Circulating CEA-Specific T Cells in Pancreatic Cancer Patients

Abstract: Carcinoembryonic antigen (CEA) is a candidate target for cellular immunotherapy of pancreatic cancer (PC). In this study, we have characterised the antigen-specific function of autologous cytotoxic T lymphocytes (CTL) specific for the HLA-A2 restricted peptide, pCEA691–699, isolated from the peripheral T cell repertoire of PC patients and sought to determine if ex vivo PD-L1 & TIM3 blockade could enhance CTL function. CD8+ T cell lines were generated from peripheral blood mononuclear cells (PBMCs) of 18 HLA-A2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…23 Certain assays have shown that targeting PD-(L)-1 can enhance T cell activation induced by TIM-3 blockade. 9,16,[29][30][31] However, since we did not observe enhanced IFN-γ production with M6903 and anti-PD-L1 combination therapy, the CEF assay may not be the best indicator of PD-(L)-1 blockade-induced IFN-γ production, and TGF-β may contribute significantly in such an assay. In order to confirm the contribution of TGF-β, recombinant human TGF-β1 (rhTGF-β1) was added in the CEF assay and its effect on IFN-γ production and M6903 activity was assessed (Figure 3c).…”
Section: M6903 Enhances T Cell Activation In Vitro As a Monotherapy Omentioning
confidence: 66%
“…23 Certain assays have shown that targeting PD-(L)-1 can enhance T cell activation induced by TIM-3 blockade. 9,16,[29][30][31] However, since we did not observe enhanced IFN-γ production with M6903 and anti-PD-L1 combination therapy, the CEF assay may not be the best indicator of PD-(L)-1 blockade-induced IFN-γ production, and TGF-β may contribute significantly in such an assay. In order to confirm the contribution of TGF-β, recombinant human TGF-β1 (rhTGF-β1) was added in the CEF assay and its effect on IFN-γ production and M6903 activity was assessed (Figure 3c).…”
Section: M6903 Enhances T Cell Activation In Vitro As a Monotherapy Omentioning
confidence: 66%
“…Because the generation of specific CTL was done with peptides but without additional costimulators and antigen‐presenting cells in our experiments, it is possible that CTL induced by these specific peptides are “anergic CTL” or “non‐functional CTL” as has been shown for MART‐1/HLA A2‐specific CTL in both healthy donors and patients . A number of studies have shown that the function of in vitro‐induced CTL may be influenced by a variety of parameters such as the concentration of peptides, costimulation of antigen‐presenting cells, and overexpression of immunosuppressive molecules during in vitro stimulation …”
Section: Discussionmentioning
confidence: 98%
“…Only QVT-tet-positive CTL were detected (C). Frequency of tetramer-positive cells is shown as the percentage of total CD8 + T cells in vitro-induced CTL may be influenced by a variety of parameters such as the concentration of peptides, costimulation of antigenpresenting cells, and overexpression of immunosuppressive molecules during in vitro stimulation [22][23][24][25][26][27]. Furthermore, we identified a homologous peptide, ASV (R6Q), derived from a microbial ROS family protein.…”
mentioning
confidence: 99%
“…Recently clinical trials focused on the tumor site ongoing immune modulation and anti-PD therapy for cancer 26 , 31 . Some research groups attempted combination of anti-PD therapy, which should facilitate adoptive cell immunotherapy reaching its maximal effect to control tumor growth 32 , 33 . During activation and amplification of cytotoxic T lymphocytes in vitro, we monitored the expression level of PD-1 on T cells by flow cytometry using CD279 antibody.…”
Section: Discussionmentioning
confidence: 99%